Application of Wastewater and Biosolids in Soil: Occurrence and Fate of Emerging Contaminants - Mohapatra, D. P. (2016)
Wastewater (WW) for irrigation and application of biosolids in soil is becoming important as it is going to become very common in the near future. By 2050, the world is going to have four billion people living in water-scarce countries, making it a norm of freshwater for the cities and WW for agriculture. Further, biosolids might still be used as green biofertilizers for soils, if they are improved from an ecological point of view. However, application of biosolids in soil is argued because of the amount of organic pollutants that compromise the dynamic equilibrium of the biological systems. Therefore, information on the concentration, behavior, and cycling of organic pollutants as well as their possible degradation pathways is needed to predict, prevent, and remediate these pollutants from different sources including WW and biosolids. Among the group of organic pollutants, emerging contaminants (ECs) enter into the soil with the irrigation water from treated effluents and fertilization by biosolids. Quantification of ECs from WW and biosolids is of main importance to predict the toxic effects of WW effluents and sludge. Moreover, their incorporation into vegetables through irrigation and their magnification through natural food webs have been proved and must be monitored. This review presents information on the different sources of emerging contaminants and linking with the ecological effects they produced by reacting in the environment during various applications of WW and biosolids in soil. The available methods for analysis and quantification of ECs in different matrices, such as WW and biosolids, are also presented.